Are advanced economies at risk of falling into debt traps? - Dabrowski, Marek (Brussels, 2016)
"One of the consequences of the global financial crisis has been rapid growth in public debt in most advanced economies. This Policy Contribution assesses the size of public debt in advanced economies and considers the potential consequences of sovereign insolvency."